PERBANDINGAN HUKUM INDONESIA DAN AUSTRIA TERHADAP PERATURAN KESEJAHTERAAN HEWAN DALAM PENGANGKUTAN HEWAN TERNAK - Pebtry Purnama Sari; Rasji Rasji (Jurnal Hukum Adigama, 2021)
Every year, various livestock animals are transported using various modes of land and sea transportation, from and to various regions, both domestically and abroad. Considering that there are still potential violations of animal welfare in the stage of transporting animals by mode of transportation in Indonesia. And there is still little public concern for livestock that is transported improperly because they think that livestock is only for consumption and the benefit of humans. Whereas farm animals are also living creatures that have the right to live and be treated properly. whether the legal regulations in Indonesia have been able to provide welfare for the transportation of livestock and obtain the rights of these animals. So this paper was made to find out and compare the legal regulations in Indonesia regarding animal welfare in the transportation of livestock with legal regulations in Austria, considering that Austria is considered as one of the countries that have a good level of welfare for animals.